COVID-19: Changing Trends and Its Impact on Future of Dentistry - Parin Bhanushali; Farhin Katge; Shantanu Deshpande; Vamsi Krishna Chimata; Shilpa Shetty; Debapriya Pradhan (International Journal of Dentistry)
The outbreak of coronavirus disease 2019 (COVID-19) rapidly escalated into a worldwide pandemic, creating a global health and economic crisis. It is a novel virus which is distinct from SARS-CoV and MERS-CoV, with Chinese horseshoe bats being the most probable origin. Transmission occurs primarily through droplet spread or contact routes. Due to the characteristics of dental settings, the risk of cross infection between dental health care personnel (DHCP) and patients can be very high. This article provides a brief overview of the structure of the virus, modes of transmission, and clinical features of COVID-19 disease. The aim of this article is to recommend infection control strategies and patient management protocols to provide optimum dental care and simultaneously prevent nosocomial infection in dental settings.